1984
DOI: 10.2307/1541159
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Parthenogenesis in Starfish Eggs: Production of Parthenogenetic Development Through Suppression of Polar Body Formation by Methylxanthines

Abstract: Methylxanthines such as caffeine, theophylline, and theobromine at 6 to 10 mM activated eggs of the starfish, Asterina pectinifera. Up to one hour of methylxanthine treatment induced parthenogenetic development in more than 80% of the eggs that failed to form the second polar body. Eggs that formed two polar bodies did not cleave. Compared with normally fertilized eggs the first cleavage in parthenogenetically developing eggs was delayed by 2 h in eggs lacking a polar body, and by 3 h in eggs with one (first) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The relative effectiveness of the three treatments probably relates to mechanisms of action, e.g., inhibition of microfilament formation [CB (Schatten and Schatten,198 I)] or spindlelkinetochore attachment [heat, caffeine (Zinkowski et al, 1989)l. All have been used successfully to inhibit polar body formation in other bivalve molluscs (Durand et al, 1990;Gosling and Nolan, 1989;Longo, 1972;Obata and Nemoto, 1984;Stanley et al, 1981). The dose of CB used for this study was lower than that typically used by other investigators (0.5 pglml vs 1 -10 pglml).…”
Section: %Ing and Suppression Of Meiotic Eventsmentioning
confidence: 97%
See 2 more Smart Citations
“…The relative effectiveness of the three treatments probably relates to mechanisms of action, e.g., inhibition of microfilament formation [CB (Schatten and Schatten,198 I)] or spindlelkinetochore attachment [heat, caffeine (Zinkowski et al, 1989)l. All have been used successfully to inhibit polar body formation in other bivalve molluscs (Durand et al, 1990;Gosling and Nolan, 1989;Longo, 1972;Obata and Nemoto, 1984;Stanley et al, 1981). The dose of CB used for this study was lower than that typically used by other investigators (0.5 pglml vs 1 -10 pglml).…”
Section: %Ing and Suppression Of Meiotic Eventsmentioning
confidence: 97%
“…Oocytes were activated by the addition of sperm (i.e., fertilized) or potassium ions (KC1-activated, 1 volume of 0.52 M KC1 to 9 volumes of oocyte suspension) (Allen, 1953;Dube and Guemer, 1982) and rinsed of excess sperm or KC1 after an 8 min exposure. Four methods were employed to suppress polar body formation: cytochalasin B (Allen, 1987), caffeine (Obata and Nemoto, 1984), heat shock (Gosling and Nolan, 1989), and combined caffeinelheat shock (Durand et al, 1990). Oocytes were cultured for 20-24 h following experimental treatments, and the percentage of Dstage and abnormal larvae were recorded.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…2E) were used for the electric fusion process. It is known that a normally matured egg with both PB1 and PB2 will not cleave even after activation without sperm, indicating the absence of reproductive centrioles (Obata and Nemoto, 1984;Washitani-Nemoto et al, 1994;Tamura and Nemoto, 2001;Uetake et al, 2002).…”
Section: Preparation Of Mature Eggs As Centrosome Recipientsmentioning
confidence: 99%
“…Artificial parthenogenesis in starfish was pioneered in the early 1980s by Obata and Nemoto (Obata and Nemoto, 1984) and later, Washitani-Nemoto et al (Washitani-Nemoto et al, 1994) found that suppression of polar body (PB) extrusions in artificially activated oocytes induces parthenogenetic development, whereas eggs that matured normally did not develop, even with artificial activation. They suggested that the meiotic centrosomes retained in the eggs by the failure of PB extrusion are diverted to mitosis-organizing centers in the mitotic spindle, resulting in parthenogenetic development.…”
Section: Introductionmentioning
confidence: 99%